Modelling and Active Control Designing of Trolleybus Catenary-Pantograph System. Issue 21 (2016) - Chen, Min; Ward, Christopher P.; Hubbard, Ella-Mae; Hubbard, Peter
Abstract: This paper introduces the 'Active Control of Trolleybus Current Collection Systems (ACTCCS)' research project and a number of early key finding. The goals of this project are to address key operational issues of a trolleybuses catenary-pantograph system in terms of the loss of contact force that causes electrical arcing, power reduction and de-wirement. The causes of this loss of contact force and the proposed solution of an actively controlled pantograph are presented in this paper through dynamic modelling and simulation of trolleybuses catenary-pantograph interaction and the application of an LQI controller. The results show that loss of contact can be eliminated with a small actuation force and this can be traded off against catenary wire displacement.